2014
DOI: 10.1063/1.4897115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the chemical treatments on the characteristics of natural cellulose

Abstract: Abstract. In order to characterize the morphology and size distribution of the cellulose fibers, natural cellulose from kenaf bast fibers was extracted using two chemical treatments; (1) alkali-bleaching-ultrasonic treatment and (2) alkalibleaching-hydrolysis. Solutions of NaOH, H 2 O 2 and H 2 SO 4 were used for alkalization, bleaching and hydrolysis, respectively. The hydrolyzed fibers were centrifuged at a rotation speed of 10000 rpm for 10 min to separate the nanofibers from the microfibers. The separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…3). The trend of formation of the kenaf fiber surface structure due to alkalization has also been reported [20]. But the structure is dependent upon the alkalization condition.…”
Section: Morphology Of the Fibersmentioning
confidence: 78%
See 1 more Smart Citation
“…3). The trend of formation of the kenaf fiber surface structure due to alkalization has also been reported [20]. But the structure is dependent upon the alkalization condition.…”
Section: Morphology Of the Fibersmentioning
confidence: 78%
“…But the structure is dependent upon the alkalization condition. Cellulose microfibrils would separate from each other by the high concentration of alkali solution or hot alkalization [20].…”
Section: Morphology Of the Fibersmentioning
confidence: 99%
“…While the peak at 1235 cm À1 was the characteristic peak of C-O stretching of the aryl group in lignin. 25 These peaks indicated that lignin and hemicelluloses existed in the untreated ber specimens.…”
Section: Resultsmentioning
confidence: 98%